Robopocalypse : a novel - Wilson, Daniel H. (Daniel Howard), 1978- (New York : Doubleday, 2011)
Two decades into the future humans are battling for their very survival when a powerful AI computer goes rogue, and all the machines on earth rebel against their human controllers.
Part one: isolated incidents. Tip of the spear -- Freshee's frogurt -- Fluke -- Hearts and minds -- Super-toys -- See and avoid -- Phreak -- Roughneck Part two: zero hour. -- Number cruncher -- Demolition -- highway 70 -- Gray horse -- Twenty-two seconds -- Avtomat -- Memento mori -- Hero material -- Part three: survival. Akuma -- Gray horse army -- Fort Bandon -- Chaperone duty -- Tickler -- Band-e-Amir -- Backbone -- Part four: awakening. Transhuman -- Call to arms -- The cowboy way -- Awakening -- The veil, lifted -- Odyssey -- Part five: retaliation. The fate of Tiberius -- Freeborn -- They shall grow not old -- Dyad -- Machines of loving grace
Keywords: Robots -- Fiction; Artificial intelligence -- Fiction; Suspense fiction; Science fiction